Characterization Of A Three-Dimensional Etched Groove Separation Of Adjacent Optical Waveguides - Masoudi, Husain M. (2000)
A technique for inhibiting the optical channel interaction between two waveguides of a three-dimensional directional coupler structure is investigated. The technique, which uses an etched groove (slot) in the space between the channels, proved to be much more effective compared to the classical method of bending the waveguides away from each other to terminate interaction. Using the three-dimensional explicit finite-difference beam-propagation method, the characteristic parameters of the etched groove have been studied carefully to find the optimum case. We also show that the application of the groove is always accompanied by a small radiation power loss.